Orion Pax’s Heroic Transformation under Oppression Using Vogler’s Hero’s Journey in Transformers One (2024) Movie - Amalia, Amira Raihana; Mujani, Sahril; Nawakwulan, Lyla (STIBA IEC JAKARTA, 2025)
The research aims to identify Orion Pax’s journey to regain liberation from constricted environments that undervalued him as a miner and undermined him as lower class. Using a qualitative descriptive approach, the research identified 10 of the 12 phases of Orion Pax's transformation as a step towards his final transformation into Optimus Prime. The findings reveal that Orion oppressive environment undervalues him as a defective bot with no cog to urge him to yearn for a new life. Along the journey, he learns of Sentinel Prime's crimes, which motivate him to fight for his freedom, only to be betrayed by D-16, resulting in his untimely death. His resurrection as Optimus Prime restored the balance to Cybertron and abolished the rigid structure of Cybertron society. Ensuring freedom to the miner class of Cybertron with a new vision of equality. This study argues that Vogler’s Hero’s Journey is not bound to the traditional self-discovery structure but instead can be applied to a non- human character in oppressive settings, providing new perspectives on class struggle, labour exploitation and freedom. The study contributes to the enrichment of the narrative and literary fields in Hero’s journey transformation in the Transformer Universe field.